Dentists as Primary Care Providers: Expert Opinion on Predoctoral Competencies - Gordon, Sara C.; Kaste, Linda M.; Mouradian, Wendy E.; Beemsterboer, Phyllis L.; Berg, Joel H.; Murdoch-Kinch, Carol Anne (Frontiers in Dental Medicine, 2021)
Dentistry and medicine traditionally practice as separate professions despite sharing goals for optimal patient health. Many US residents experience both poor oral and general health, with difficulty accessing care. More efficient collaboration between these professions could enhance health. The COVID-19 pandemic disclosed further disparities while underscoring concerns that physician supply is inadequate for population needs. Hence, enhancing healthcare provider education to better meet the public's health needs is critical. The proposed titles “Oral Physician” or “Oral Health Primary Care Provider” (OP-PCP) acknowledge dentist's capacity to diagnose and manage diseases of the orofacial complex and provide some basic primary healthcare. The US Surgeon General's National Prevention Council and others recommend such models. Medical and dental education already overlap considerably, thus it is plausible that dental graduates could be trained as OP-PCPs to provide primary healthcare such as basic screening and preventive services within existing dental education standards. In 2018, 23 dental and medical educators participated in an expert-opinion elicitation process to review educational competencies for this model. They demonstrated consensus on educational expansion and agreed that the proposed OP-PCP model could work within existing US Commission on Dental Accreditation (CODA) standards for predoctoral education. However, there were broader opinions on scope of practice details. Existing CODA standards could allow interested dental programs to educate OP-PCPs as a highly-skilled workforce assisting with care of medically-complex patients and to helping to reduce health disparities. Next steps include broader stakeholder discussion of OC-PCP competencies and applied studies including patient outcome assessments.